The Influence of Motivation and Competence on Teacher Performance: A Narrative Literature Review - Dwi Ferdiyatmoko Cahya Kumoro; Esra Silalahi; Ima Nazmia; Masduki Asbari (Yayasan Aya Sophia Indonesia, 2023)
The purpose of writing this article is a narrative literature review of 3 articles that discuss the effect of teacher motivation and competence on teacher performance with the aim of identifying and summarizing previously published articles without any criticism for articles reviewed in achieving the goals and objectives to be achieved by the ministry of education. need to pay attention to teacher performance which is influenced by motivation and competence on teacher performance. The review of the article shows that the influence of motivation and competence on teacher performance has a positive impact.